2005
DOI: 10.1159/000086172
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Caffeine, Performance and Mood: Enhancing and Restorative Effects after Controlling for Withdrawal Reversal

Abstract: This study aimed to determine whether sustained (i.e. dietary) use of caffeine has net effects on performance and mood compared with sustained abstinence, and whether dietary caffeine restores performance and mood adversely affected by sleep restriction. Participants (n = 96) alternated weekly between ingesting placebo and caffeine (1.75 mg/kg) three times daily for 4 consecutive weeks, while either rested or sleep restricted. Performance involved either a single task requiring sustained vigilance or a varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 59 publications
3
26
1
Order By: Relevance
“…Whereas a number of previous studies found decrements in performance associated with caffeine withdrawal and reversal of performance decrements when caffeine is re-ingested [23,38,45,46,59] , no such withdrawal and reversal of withdrawal effects were observed during task performance in the present study. The absence of caffeine-induced performance effects in the present study could have been due to the presence of ceiling effects.…”
Section: Discussioncontrasting
confidence: 98%
See 3 more Smart Citations
“…Whereas a number of previous studies found decrements in performance associated with caffeine withdrawal and reversal of performance decrements when caffeine is re-ingested [23,38,45,46,59] , no such withdrawal and reversal of withdrawal effects were observed during task performance in the present study. The absence of caffeine-induced performance effects in the present study could have been due to the presence of ceiling effects.…”
Section: Discussioncontrasting
confidence: 98%
“…The extended paradigm and versions of it have been employed in various studies of caffeine-induced effects on performance, mood, cardiovascular reactivity, and sleep [23,41,42,[44][45][46] . The paradigm includes four consecutive 1-week periods ( table 1 ), with a strictly prescribed and biologically verified regimen of caffeine intake or abstinence for every day of each week.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, we found no meta-analysis on caffeine cognitive effects in healthy adults. In a review, James et al [161] concluded that appropriately controlled studies show that its apparent beneficial effects on performance and mood are almost wholly attributable to reversal of the withdrawal effects that occur after short periods of abstinence (e.g. overnight).…”
Section: Melatonininergicsmentioning
confidence: 99%